Paciente masculino de 65 años con diagnóstico de insuficiencia respiratoria aguda por Covid 19 - Barco Pallete, Héctor Adrián (2021)
The disease (COVID-19) is a respiratory tract infection caused by a new-onset coronavirus that was first identified in Wuhan, China in December 2019. The genetic sequence of the virus indicates that it is a closely related beta coronavirus of the SARS virus, the objective of this clinical case is to describe the clinical picture of respiratory failure by COVID-19 and its epidemiology in a male patient aged 65 years, this study has an experimental method and this work is justified due to the high index of cases reported by COVID-19 since within patient care the role of the respiratory therapist is fundamental, our theoretical support is determined by the following topics: Respiratory Failure, Coronavirus and Acute Respiratory Syndromes, Covid-19 including that through complementary tests we can reach the diagnosis of the disease and that the administration of oxygen in patients who are diagnosed with Covid -19 is essential, since this disease is respiratory. On December 31, 2019, the Wuhan Municipal Health and Sanitation Commission reported the existence of 27 cases of pneumonia of unknown etiology with onset of symptoms, on December 8, including 7 severe cases, with common exposure to a market seafood, fish and live animals in the city of Wuhan. On January 7, 2020, the Chinese authorities identified as the causative agent of the outbreak a new type of virus from the Coronaviridae family, temporarily called “new coronavirus”, 2019-nCoV. On January 30, 2020, the World Health Organization (WHO) declares the outbreak an international emergency.